2003
DOI: 10.1176/jnp.15.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Visual Evoked Potential Changes in Alzheimer's Disease

Abstract: Previous studies have consistently found a selective delay of the P2 flash visual evoked potential (VEP) component among groups of patients with Alzheimer's dementia (AD) compared with control groups. Several authors have termed the selective P2 delay a "marker" for AD and have called for its use in clinical diagnosis. This study examined the diagnostic utility of the selective P2 delay in a retrospective sample of 45 AD patients and 60 age-equivalent healthy control subjects. Although significant between-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…Previous studies of visual evoked responses in AD have reported delays of the later component (our P2 waveform) of flash 25,37 and pattern reversal 38,39 EPs. The pattern onset stimuli used in our studies are unlikely to yield exactly the same responses as flash or pattern reversal stimuli.…”
Section: Figurementioning
confidence: 65%
“…Previous studies of visual evoked responses in AD have reported delays of the later component (our P2 waveform) of flash 25,37 and pattern reversal 38,39 EPs. The pattern onset stimuli used in our studies are unlikely to yield exactly the same responses as flash or pattern reversal stimuli.…”
Section: Figurementioning
confidence: 65%
“…These findings suggest strongly that the P2 delay carries AD specific information. The primary impediment to use of this delay as a diagnostic aid for evaluating individual patients is the large overlap of the P2 latency distributions of the groups (Coburn et al, 2003). The present study was undertaken principally in an attempt to refine stimulation and recording methodologies in order to reduce P2 latency variability.…”
Section: Implications For Ad Diagnosismentioning
confidence: 99%
“…Even in studies replicating such between-group differences, a substantial overlap of latency distributions makes separation of individual Alzheimer participants from individual controls unreliable. For example, a recent evaluation of the diagnostic potential of the selective P2 delay (Coburn et al, 2003) found the expected statistically significant differences between AD and healthy control groups, but the diagnostic accuracy of the delay when applied to individual participants was too low to be clinically useful. Like the failures to replicate the basic betweengroup differences, the low diagnostic classification accuracy could stem from methodological factors.…”
Section: Introductionmentioning
confidence: 99%
“…The P200 component of the flash visual evoked potential was delayed in AD patients compared to healthy controls [71,72]. Moreover, AD patients had delayed P100 latencies compared to normal controls [73][74][75].…”
Section: Visual Erpsmentioning
confidence: 86%